Acanthopagrus taiwanensis, a new sparid fish (Perciformes), with comparisons to Acanthopagrus berda (Forsskål, 1775) and other nominal species of Acanthopagrus - Iwatsuki, Yukio; Carpenter, Kent E. (Zootaxa, 2006)
A new sparid species, Acanthopagrus taiwanensis, is described on the basis of six specimens that were previously misidentified as A. berda (Forsskål, 1775), collected from Tung-kang, southwestern Taiwan. Acanthopagrus taiwanensis and A. berda are similar in overall appearance, both with deep bodies. However, A. taiwanensis differs from the latter in having a more rounded body, broadly rounded anteriormost head squamation with around 10 somewhat smaller scales anteriorly, 3 or 4 cheek scale rows, thin upper and lower lips, older individuals with a ridge on dorsal profile in front of eye and upper profile of head evenly convex, head and body black with sharply contrasting white area ventrally, a dark spot at upper base of pectoral fins, and flat molar teeth. In contrast, A. berda has a deeper body, broadly rounded anteriormost head squamation with around 20 small scales anteriorly, 5 or 6 cheek scale rows, thick upper and lower lips, larger individuals with a weak ridge in profile in front of eye and concave snout profile, head and body silvery gray, no black spot at upper base of pectoral fins and somewhat pointed molar teeth. Older individuals of A. berda also develop a strong concavity of the ventral edge of the first two infraorbitals above the posterior part of upper jaw, while the edge is relatively straight or weakly concave in A. taiwanensis. We discuss the nominal species that have been placed in synonymy with A. berda and contrast A. taiwanensis with similar congeners.